Determination of peat elasticity modulus (constrained modulus) based on field measurement using simplified consolidation model = Określenie modułu ściśliwości torfu na podstawie badań terenowych w oparciu o uproszczony model konsolidacji - Olszewska, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents methods to determine the peat elasticity modulus based on settlement measurement of the preloaded embankment. The author proposes two methods: the first does not take into consideration the strengthening of the soil as a result of the settlement and the second includes the strengthening process of soil related to the settlement.
Keywords: moduł ściśliwości; torf; nasyp na gruntach organicznych; badania terenowe; elastic modulus; peat parameter; embankment on organic soil; field measurement